A Test of the Nonlinearity Hypothesis in Great‐tailed Grackles (Quiscalus mexicanus). (17th February 2013) - Slaughter, Emily I.; Berlin, Erin R.; Bower, Jonathan T.; Blumstein, Daniel T.; Foster, S.
Abstract Highly aroused or scared animals may produce a variety of sounds that sound harsh and are somewhat unpredictable. These sounds frequently contain nonlinear acoustic phenomena, and these nonlinearities may elicit arousal or alarm responses in humans and many animals. We designed a playback experiment to elucidate whether specific nonlinear phenomena can elicit increased responsiveness in great‐tailed grackles (Quiscalus mexicanus). We broadcast two control sounds (a 0.5‐s, 3‐kHz pure tone and the song of tropical kingbirds (Tyrannus melancholicus) and three test sounds that all began with a 0.4‐s, 3‐kHz pure tone and ended with 0.1 s of either a 1‐ to 5‐kHz band of white noise, an abrupt frequency jump to 1 kHz, or an abrupt frequency jump to 5 kHz. In response to these three nonlinear phenomena, grackles decreased their relaxed behavior (walking, foraging, and preening) and increased looking. A second experiment looked at the rapidity of the time course of frequency change and found that the abrupt frequency jump from 3 to 1 kHz, as opposed to a gradual downward frequency modulation over the same bandwidth, was uniquely arousing. These results suggest that while nonlinear phenomena may be generally evocative, frequency jumps may be the most evocative in great‐tailed grackles. Future studies in other systems can evaluate this general hypothesis.